PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN DENGAN RELATIONSHIP QUALITY SEBAGAI VARIABEL INTERVENING - Endang Sri Wahyuningsih; Heri Setiawan (FEB UNWIKU PURWOKERTO, 2020)
Abstract: The recearch entitled “ The Effect of Relationship Marketing on Customer Loyality with Relationship Quality as an Intervening Variable ( Study on Arcon Concrete Tile Consumers in Purwokerto Region)” The Purpose of this study .was to investigate and analyze the effect of relationship marketing on relationship quality and customer loyality, to know and analyze the effect of relationship quality on customer loyality, and to find out and analyze the effect of relationship quality as an intervenig variable in mediating the effect of relationship marketing on customer loyalty. Analysis techniques using linear regression and Sobel test. Based on the results of a simple regression analysis of the first and second models, the t- value of relationship marketing variables is greater than the value of the table. From the results of multiple regression analysis obtained t count value of relationship quality variable is greater than the value of t table. Furthermore , based on the results of the mediation variable test with the Sobel test, the t Sobel value is greater than the t table value. Management need to implement a variety of marketing policies relating to relationship marketing and relationship quality in order to continue to increase the loyalty of its customers.